2013
DOI: 10.1007/s11669-013-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Computer Simulation of Gradient Zone Formation in WC-Ti(C,N)-TaC-NbC-Co Cemented Carbides

Abstract: The thermodynamic and diffusion databases for multi-component W-C-Co-Ti-Ta-Nb-N cemented carbides have been developed through a combination of experimental, theoretical and assessment work. Using the CALPHAD approach, the thermodynamic database has been established based on the literature information and experimental investigations. The diffusion database contains the atomic mobility parameters for different diffusing elements in liquid, which were calculated by a modified Sutherland equation. According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Increasing N content can not only lead to a wider thickness of surface layer, but also diminish the grain size. The effect of adding other cubic phases, such as TaC and NbC have been studied in previous work of [37] and [38]. It was found that when Nb was added to the cubic phase, the surface zone becomes wilder with larger depletion of Co and enrichment in cubic phase.…”
Section: Diffusion Foundations Vol 15mentioning
confidence: 99%
“…Increasing N content can not only lead to a wider thickness of surface layer, but also diminish the grain size. The effect of adding other cubic phases, such as TaC and NbC have been studied in previous work of [37] and [38]. It was found that when Nb was added to the cubic phase, the surface zone becomes wilder with larger depletion of Co and enrichment in cubic phase.…”
Section: Diffusion Foundations Vol 15mentioning
confidence: 99%